2010
DOI: 10.3402/gha.v3i0.5420
|View full text |Cite
|
Sign up to set email alerts
|

Health inequalities among older men and women in Africa and Asia: evidence from eight Health and Demographic Surveillance System sites in the INDEPTH WHO-SAGE Study

Abstract: Background Declining rates of fertility and mortality are driving demographic transition in all regions of the world, leading to global population ageing and consequently changing patterns of global morbidity and mortality. Understanding sex-related health differences, recognising groups at risk of poor health and identifying determinants of poor health are therefore very important for both improving health trajectories and planning for the health needs of ageing populations.ObjectivesTo determine the extent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 28 publications
3
38
0
2
Order By: Relevance
“…Marriage facilitates greater access to social support, which is associated with better health outcomes for married people relative to other marital statuses (Waite and Gallagher, 2001; Carr and Bodnar-Deren, 2009; Ng et al ., 2010; Herm et al ., 2016). A person who is married or co-habiting has a partner from whom he or she can request emotional support, and from whom this kind of support is socially expected as part of spousal role obligations (Cornwell, 2012).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Marriage facilitates greater access to social support, which is associated with better health outcomes for married people relative to other marital statuses (Waite and Gallagher, 2001; Carr and Bodnar-Deren, 2009; Ng et al ., 2010; Herm et al ., 2016). A person who is married or co-habiting has a partner from whom he or she can request emotional support, and from whom this kind of support is socially expected as part of spousal role obligations (Cornwell, 2012).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…[7][8][9][10][11][12] A study based on the INDEPTH WHO-SAGE data revealed how different socioeconomic indicators such as education, marital status, living arrangement and household socioeconomic status influence health inequality observed between men and women in eight countries in Africa and Asia. 7 Studies in Brazil and Mexico link inequalities in DFLE to the prevalence of NCDs. [8][9][10] In Mexico, a nearly 10-year gap in DFLE between diabetics and non-diabetics exists.…”
Section: Introductionmentioning
confidence: 99%
“…Kadınların beklenen yaşam süresi uzun olmakla birlikte, yaşlı kadınlarda morbidite daha sık ve sağlık algısı daha kötüdür (28)(29)(30). Kadınlar, erkeklerden sosyo-ekonomik olarak dezavantajlı olduklarından, kaynaklara daha zor erişebilmektedir.…”
Section: şEkil-3unclassified